Reader performance in the ultrasonographic evaluation of oropharyngeal carcinoma. (February 2018) - Faraji, Farhoud; Padilla, Ericka S.; Blitz, Dana; Wenderoth, Meghan B.; Blanco, Ray G.; Kawamoto, Satomi; Sheth, Sheila; Hamper, Ulrike M.; Fakhry, Carole
Highlights: 88% of base of tongue sonograms were identified correctly by a majority of readers. For base of tongue tumors, sensitivity, specificity, and kappa were 73%, 85%, and 0.51. 84% of palatine tonsil sonograms were identified correctly by a majority of readers. For tonsillar tumors, sensitivity, specificity, and kappa were 74%, 78%, and 0.41. Abstract: Objective: To examine reader performance in evaluating oropharyngeal anatomy on ultrasonography. Materials and methods: Ultrasound images of the oropharynx comprising normal and malignant anatomic variants were organized into slideshows. Slideshows were administered to 6 readers blinded to participant tumor status and with varying experience reading oropharyngeal sonograms. A training slideshow oriented readers to images of the oropharynx with and without malignant lesions. Readers then evaluated images in a test slideshow for tumor presence and marked orthogonal long and short dimensions of the tumor. Results were analyzed for accuracy, sensitivity, specificity, inter-reader agreement, and measurement error relative to prospectively-identified reference measurements. Results: Eighty-seven percent of base of tongue (BOT) sonograms were identified correctly by a majority of readers. In identifying BOT tumors, median accuracy, sensitivity, specificity, and Fleiss's kappa were 79%, 73%, 85%, and 0.51, respectively. Median measurement error in the long and short axes for BOT tumors was −2.6% (range: −40% to 29%) and −2.6% (range: −56% to 156%), respectively. Eighty-four percent of palatine tonsil sonograms were identified correctly by a majority of readers. In identifying tonsil tumors, median accuracy, sensitivity, specificity, and Fleiss's kappa were 77%, 74%, 78%, and 0.41, respectively. Median measurement error in the long and short axes for tonsil tumors was 3.8% (range: −45% to 32%) and −6.5% (range: −83% to 42%), respectively. Conclusions: Overall, US has clinically useful sensitivity for identification of oropharyngeal carcinoma among readers of diverse clinical backgrounds and experience. US may be useful for the evaluation of features such as tumor dimensions.